Nipple confusion-is it real? - Jamani, Nurjasmine Aida (2019)
Nipple confusion is when a breastfeeding baby is having trouble latching and breastfeeding effectively after being fed with a bottle. Hypotheses: infants unable to adapt different sucking mechanisms to switch between breast and bottle